Academy of Dental Materials guidance on in vitro testing of dental composite bonding effectiveness to dentin/enamel using micro-tensile bond strength (μTBS) approach. Issue 2 (February 2017) - Armstrong, Steve; Breschi, Lorenzo; Özcan, Mutlu; Pfefferkorn, Frank; Ferrari, Marco; Van Meerbeek, Bart
Abstract: Objective: An ideal dental adhesive should provide retentive strength, marginal seal, be relatively simple to achieve and demonstrate clinical durability. Future improvements in adhesive bonding to tooth structure require in vitro test methods that provide reliable data for materials development and/or evaluation of experimental variables. The objective of this project was to identify a test method that is relatively easy to perform, repeatable and ultimately useful for predicting clinical outcomes. Methods: The Academy of Dental Materials initiated a project to develop and distribute guidance documents on laboratory test methods that are useful for the evaluation of dental adhesives and cements, composite resins and ceramics. Results: The dental adhesive sub-group has identified the micro-tensile bond strength test, especially after subjecting the specimens to a durability challenge, as currently the best practical surrogate measure of dental composite restoration retention. Conclusion: The following μTBS guidance is meant to aid the researcher in conducting the μTBS test. The authors, while recognizing the limitations of a static, strength-based test method, welcome comments and suggestions for improvements of this guidance document in future revisions.